РІВЕНЬ І ЯКІСТЬ ЖИТТЯ НАСЕЛЕННЯ ЯК РЕЗУЛЬТАТ ЗБАЛАНСОВАНОГО РОЗВИТКУ РЕГІОНУ - Savchenko, T.G.; Kulyak, A.I.; Kulyak, I.I. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2013)
The content of the concept “standard of living and quality of population life” is discussed. Basic criteria and indicators that characterize standard of living and quality of population life are identified. The relationship between the indicators and population life quality is generalized, and the corresponding statistical data are analyzed. REFERENCES: